Medical termination of pregnancy in bitches using progesterone receptor blocker - KULASEKAR, K; JOSEPH, CECILIA; RANGASAMY, S (The Indian Journal of Animal Reproduction, 2023)
This trial was undertaken to test the efficacy of progesterone receptor blocker, Mifepristone (Tab.Mifeprin-200 mg, Sun Phannaceuticals, Mumbai) in terminating pregnancy in bitches. Ten pregnant bitches brought to the Madras Veterinary College Hospital for medical termination of pregnancy were administered Mifepristone at the dose rate of2.5mg/Kg body weight bid orally for 4-5 days. Ultrasonography was done to confirm pregnancy and to monitor fetal viability and resorption after induction of treatment. In all bitches, pregnancy was terminated between 3-6 with a mean of 4.5 ± 1.5 days after treatment and there was no side effect associated with the treatment. Mifepristone administration is a safe and reliable method to terminate unwanted pregnancy in dogs.